2007
DOI: 10.1080/14763140701491294
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical comparison of dominant and non-dominant arm throws for speed and accuracy

Abstract: Training a non-dominant limb may increase a competitor's ability to perform with either side of his or her body and confer an advantage over competitors that use one side of the body exclusively. The aim of this study was to determine the kinematic differences between dominant and non-dominant arm throwing techniques for speed and accuracy in Under-17 and Under-19 high-performance cricketers. Seven participants performed ten throws for each arm (dominant/non-dominant) and condition (speed/accuracy) at a target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 15 publications
(20 reference statements)
4
32
0
Order By: Relevance
“…Significant differences in the performance and kinematics between preferred and non-preferred upper-limb movements, such as overarm throwing, have been reported (referred to as dominant and non-dominant in these studies, Hore, Watts, Tweed, & Miller, 1996;Ning, Faro, Sue, & Hamilton, 1999;Sachlikidis & Salter, 2007;van den Tiller & Ettema, 2006;Williams, Haywood, & Painter, 1996). Throwing performance has been reported as superior in the preferred arm for both accuracy (Hore et al, 1996) and throw velocity (Ning et al, 1999;van den Tiller & Ettema, 2006).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Significant differences in the performance and kinematics between preferred and non-preferred upper-limb movements, such as overarm throwing, have been reported (referred to as dominant and non-dominant in these studies, Hore, Watts, Tweed, & Miller, 1996;Ning, Faro, Sue, & Hamilton, 1999;Sachlikidis & Salter, 2007;van den Tiller & Ettema, 2006;Williams, Haywood, & Painter, 1996). Throwing performance has been reported as superior in the preferred arm for both accuracy (Hore et al, 1996) and throw velocity (Ning et al, 1999;van den Tiller & Ettema, 2006).…”
Section: Introductionmentioning
confidence: 90%
“…Throwing performance has been reported as superior in the preferred arm for both accuracy (Hore et al, 1996) and throw velocity (Ning et al, 1999;van den Tiller & Ettema, 2006). In addition, non-preferred throws have been described as displaying a less optimal coordination pattern (Sachlikidis & Salter, 2007), with movement patterns similar to those exhibited by novice performers (Williams et al, 1996). van den Tiller and Ettema (2006) reported an increased internal rotation velocity and an increased range of internal rotation movement of the shoulder in throwing with the preferred arm.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Furthermore, several studies investigated the differences between the dominant and non-dominant side during the throwing motions. It was reported that the non-dominant sides have slower ball speeds, decreased shoulder external rotation, elbow flexion, shoulder internal rotation and increased lateral flexion and shoulder abduction (Sachlikidis & Salter, 2007;van den Tillaar & Ettema, 2009). However, these studies only compared the differences between the dominant and non-dominant side.…”
Section: Introductionmentioning
confidence: 96%